Mitochondrial tRNA(Leu(UUR)) gene mutation diabetes mellitus in Chinese - Xiang, K; Wang, Y; Wu, S; Lu, H; Zheng, T; Sun, D; Weng, Q; Jia, W; Shen, W; Pu, L; He, J (Chinese medical journal, 1997)
To ascertain the prevalence and clinical features of mitochondrial tRNALeu(UUR) gene nucleotide (nt) 3243 A-->G mutation diabetes mellitus in Chinese and to establish the approaches for genetic diagnosis of this subtype of diabetes during routine daily clinical practice. Mitochondrial nt 3243 A-->G mutation was screened among 207 unrelated non-insulin-dependent diabetes mellitus (NIDDM) patients by using polymerase chain reaction (PCR)/Apa I restriction endonuclease digestion. Samples with positive result were confirmed by DNA sequence analysis. Genetic and clinical analysis were carried out in family members of the proband with positive genetic diagnosis. Positive results were found in two subjects during screening of unrelated NIDDM patients, which account for 2.4%-11.1% of NIDDM subjects with uncommon clinical features (with early age-of-onset, with low body-mass-index and on insulin therapy) or with positive family history of diabetes consistent with or unable to exclude from maternal inheritance. Genetic diagnosis was positive in 10 out of 25 family members in the pedigrees of these two probands. Mitochondrial tRNALeu(UUR) gene nt 3242 A-->G mutation should be considered in diabetic patients with the above-mentioned clinical features. The genetic diagnosis in daily clinical practice can be performed with allele specific priming amplification, or PCR/Hae III or Apa I digestion which are technically simple to perform and diagnostically easy to define.